A novel MLPH variant in dogs with coat colour dilution. (19th January 2018) - Bauer, A.; Kehl, A.; Jagannathan, V.; Leeb, T.
Summary: Coat colour dilution may be the result of altered melanosome transport in melanocytes. Loss‐of‐function variants in the melanophilin gene ( MLPH ) cause a recessively inherited form of coat colour dilution in many mammalian and avian species including the dog. MLPH corresponds to the D locus in many domestic animals, and recessive alleles at this locus are frequently denoted with d . In this study, we investigated dilute coloured Chow Chows whose coat colour could not be explained by their genotype at the previously known MLPH :c.–22G>A variant. Whole genome sequencing of such a dilute Chow Chow revealed another variant in the MLPH gene: MLPH :c.705G>C. We propose to designate the corresponding mutant alleles at these two variants d 1 and d 2 . We performed an association study in a cohort of 15 dilute and 28 non‐dilute Chow Chows. The dilute dogs were all either compound heterozygous d 1 /d 2 or homozygous d 2 /d 2, whereas the non‐dilute dogs carried at least one wildtype allele D . The d 2 allele did not occur in 417 dogs from diverse other breeds. However, when we genotyped a Sloughi family, in which a dilute coloured puppy had been born out of non‐dilute parents, we again observed perfect co‐segregation of the newly discovered d 2 allele with coat colour dilution. Finally, we identified a blue Thai Ridgeback with the d 1 /d 2 genotype. Thus, our data identify the MLPH :c.705G>C as a variant explaining a second canine dilution allele. Although relatively rare overall, this d 2 allele is segregating in at least three dog breeds, Chow Chows, Sloughis and Thai Ridgebacks.